STAR TREK COSTUMES : FIVE DECADES OF FASHION FROM THE FINAL FRONTIER - Block, Paula M.; Erdmann, Terry J.; BLACKMAN, ROBERT (San Rafael, California : Insight Editions, 2015)
Block and Erdmann showcase the unique costumes of the Star trek saga, taking in fifty years of iconic and hugely influential designs. From the classic Starfleet uniforms and daringly provocative outfits of the original series to Vulcan robes and Klingon attire, the book celebrates the artistry that has made the Star trek costumes as innovative and imaginative as its futuristic technologies.
Includes bibliographical references (page 255)
Keywords: Star trek (Television program).; Star Trek films; Costume; Fashion in motion pictures; Clothing and dress on television